Murda Khanay Mein Aurat, the Voice of the Minority’s Tragedy - Hassan, Ali (sourcecoder, 2022)
The majority has always oppressed the minority. Sometimes in the name of religion, due to dress and name, regarding religious buildings, the minority has been persecuted and this process is still going on. This problem is not of a single country and a religion, but it is a global problem. The minority whether the Muslim, the Hindu, or Jew has to bow down before the atrocities of the majority. Literature is representative of society, so efforts are being made to express minority issues in literature at the global level. The novel “Murda Khanay Mein Aurat” is a part of such efforts.